1990
DOI: 10.1177/009770049001600201
|View full text |Cite
|
Sign up to set email alerts
|

International Links and the Socioeconomic Development of Rural China

Abstract: exists in different versions, but all share one common thesis: economic links between a developing nation and one or more developed nations have been, and will always be, detrimental to the evolution of the former.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The solidarity and functioning of these 'old-fashion' organisations are supposed to be undermined by the 'new' forces of globalisation. However, recent studies have revealed that the Chinese diaspora are able to reorganise their voluntary associations to meet the challenges of globalisation (Woon, 1990;Liu, 1998). In a process known as transnationalism, Chinese diaspora have managed to build effective transnational business networks that stretch from their place of origin ( giaoxiang) to their place of settlement (Lever-Tracy, Ip and Tracy, 1996;Smart and Smart, 1998).…”
Section: Spatial Mobility Under Globalisationmentioning
confidence: 99%
“…The solidarity and functioning of these 'old-fashion' organisations are supposed to be undermined by the 'new' forces of globalisation. However, recent studies have revealed that the Chinese diaspora are able to reorganise their voluntary associations to meet the challenges of globalisation (Woon, 1990;Liu, 1998). In a process known as transnationalism, Chinese diaspora have managed to build effective transnational business networks that stretch from their place of origin ( giaoxiang) to their place of settlement (Lever-Tracy, Ip and Tracy, 1996;Smart and Smart, 1998).…”
Section: Spatial Mobility Under Globalisationmentioning
confidence: 99%
“…Until now, academic work on local Chinese emigrant communities and the return of emigrants have primarily focused on the local socio‐economic effects of remittances and investments (see, e.g., Watson, 1975; Woon, 1989, 1990), on traditional cultural forms such as the lineage structure in Southern China or on moral and social dilemmas related to returning villagers (Watson, 1975; Oxfeld, 2004), and on returned ethnic Chinese refugees ( guiqiao ) from South‐East Asia to designated Overseas Chinese State Farms (Peterson, 2012). In the context of the migrants’ return, emigration areas have as such been more likely to be conceived as static and primarily undergoing change and development due to the influence of dynamic emigrants.…”
Section: New Mobilities By Chinese Descendants To China’s Megacitiesmentioning
confidence: 99%
“…In Duanfen, as in other parts of Taishan, out-migration, as opposed to entrepreneurship, is the goal of rural households. The so-called`Overseas Chinese mentality' is obsessed by the possibility of a better life abroad (Johnson and Woon, 1997;Woon, 1990).…”
Section: The Western Delta: Taishan the Overseas Chinese Connectionmentioning
confidence: 99%